Pharmacist intervention can reduce the potential use of inappropriate drugs medications in Indonesian geriatric patients - Endang Darmawan&, Hidayat Ahmad&, Dyah Aryani Perwitasari&, Nurul Kusumawardani& (Journal of Applied Pharmaceutical Science, 2020)
Intervention study design by pharmacists to doctors using face-to-face interviews conducted in this study aims to analyze potentially inappropriate medications (PIMs) with prospective data collection in the geriatric ward of Regional General Hospital Dr.M. M. Dunda Gorontalo, Indonesia in the period from January to March 2018. The sampling technique was a total sampling design and obtained by the end of the study were 123 patients. Results of analysis with Beers and screening tool of older people’s prescriptions (STOPP) from 123 patients found 54 PIMs in 48 patients (39.0%) based on Beers criteria and 6 patients (6.3%) based on STOPP criteria. Bivariate analysis showed that there was a significant relationship between the incidence of adverse drug events (ADEs), with unresolved PIMs with a relative risk value at 1.55 (95% CI 1.26:1.91), p = 0.007 and a correlation coefficient (r) of 0.332. Based on the results of univariate and bivariate statistical analysis, it can be concluded that there are still many PIMs occurring in the prescription of geriatric patients based on Beers and STOPP criteria and pharmacists have a large enough role to reduce the incidence of PIMs so that the prevalence of ADEs due to inappropriate use of the drug can be minimized at Regional General Hospital Dr. M. M. Dunda Gorontalo, Indonesia.
Keywords: Pharmacists, geriatric, Beers criteria, STOPP criteria, adverse drug events.